3D in utero quantification of T2* relaxation times in human fetal brain tissues for age optimized structural and functional MRI - Blazejewska, Anna I (Magn Reson Med, 2016)
PURPOSE: Maximization of the BOLD fMRI contrast requires TE of the MR sequence to match the T2* value of the tissue of interest, which is expected to be higher in the fetal brain compared to a child or an adult. METHODS: T2* values of the cortical plate/cortical grey matter tissue in utero in healthy fetuses from mid-gestation onwards (20–36 GW) were measured using 3D T2* maps calculated from 2D dual-echo T2*-w data corrected for between-slice motion and reconstructed in 1.0 mm(3) isotropic resolution from a sequence of multiple time points, together with 1.0 mm(3) isotropic resolution T2-w structural data. RESULTS: Mean T2* relaxation times of the cortical tissue were about two times higher than previously reported in adults. In a supporting single seed analysis experiment default mode and auditory networks appeared better localized and less noisy while using TE=100 ms versus TE=43 ms. The results of the previous study reporting a trend for T2* values to decrease with fetal age were reproduced and extended to include subjects in earlier gestation (20–26 GW) and cortical tissues. CONCLUSIONS: The first measurement of T2* values in fetal cortical tissues suggested the appropriate TE range for fetal BOLD fMRI protocol optimization to be 130–190 ms.